Ex-Officio Rights in Talak Divorce: (UINSI Samarinda, 2022)
Abstract Theoretically, judges have the ex-officio rights to protect the rights of women and children in divorce cases. This study examines the judges' considerations in applying Ex officio rights associated with the plaintiff's profession as Pegawai Negeri Sipil (PNS, Indonesian Civil Servant) and non-civil servant. This normative legal research employed a case study and conceptual approach. The data collection techniques of this study were obtained from interviews, document content, and literature review. This study highlighted several essential points. First, the judges’ reasoning for applying ex-officio rights, which is referred to the Article 41 paragraph (c) of Law Number 16 of 2019 and the Decree of the Chairman of the Supreme Court Number: KMA/032/SK/IV/2006 concerning the Enforcement of Guidelines for Administration of Justice in Court. Second, the judges’ decision did not contradict the Ultra Petita principle since the considerations are based on logical arguments and facts such as the husband’s earning capacity, the wife’s devotion, and the wife’s loyalty. The legal basis of judges' decisions on divorce cases involving civil servants is similar to ordinary divorce cases. The divorce case is only distinguished by the addition of the regulations concerning civil servants in the divorce case of civil servants. Keywords: Ex-Officio, Ex-wife Rights, Judges’ Considerations, Talak, Civil Servant